Pengaruh Literasi Keuangan, Perilaku Keuangan dan Toleransi Risiko Terhadap Keputusan Berinvestasi Mahasiswa Melalui Aplikasi Ajaib - Sulasih, Sulasih; Anjani, Wiwin (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study examines the influence of financial literacy, financial behavior, and risk tolerance on students’ investment decisions when using the Ajaib application. A quantitative research design was employed with a sample of 343 students who actively invest through the platform. Data were collected using a structured questionnaire and analyzed using Multiple Regression Analysis with IBM SPSS. The empirical results indicate that financial literacy and financial behavior both have a positive and significant influence on investment decisions. In contrast, risk tolerance shows a negative and significant effect, suggesting that students with lower tolerance for risk tend to adopt more cautious investment strategies. Furthermore, the three variables collectively demonstrate a significant simultaneous effect on investment decision-making. These findings highlight the importance of strengthening financial knowledge and responsible financial practices to enhance rational investment behavior, particularly among novice student investors using digital investment platforms